(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Hypertension (high blood pressure) is one of the cardiovascular diseases, and its early detection and management play a critical role in healthcare. Hypertension is associated with numerous physical and social factors, and its prevention is possible through early diagnosis and continuous monitoring. In patients covered by medical insurance packages, the role of a patronage nurse is significant in consistently monitoring blood pressure, providing patients with qualified advice, and improving treatment effectiveness. Research highlights the necessity of a comprehensive approach to combating hypertension and emphasizes the importance of its early detection for public health.